Effects of root extract of Ashwagandha, Withania somnifera, on function of thyroid in cockerel - PANDA, SUNANDA; KAR, ANAND (The Indian Journal of Animal Sciences, 2013)
Importance of root extract of Ashwagandha, Withania somnifora (Solanaceae), in thyroid function has been studied inÂ cockerels. Its root extract (20 mg/day/animal for 30 days) increased serum thyroxine (T4 ) concentrations suggesting its prothyroidic action. However, triidothyronine (T3 ) conce;ntrations and T3 :T4 ratio were not altered significantly indicating little or no role of this plant in extrathyroidal (fonversion of T4 toÂ T3 ’ the major source of T3 generation. The drug also increased the plasma protein concentrations.